Leading collaborative architectural practice - Carraher, Erin 1979-; Smith, Ryan E.; DeLisle, Peter 1949- (John Wiley & Sons, Inc., 2017)
"The book is structured in five parts that present the history and contemporary conditions that shape today's building industry, the tools and tactics needed to develop and foster collaboration amongst various project stakeholders, and explores the changing nature of the workforce, emerging technologies, and innovative business models that will impact the future of our practice. Each of the parts is briefly outlined below"--Provided by publisher.